Disentangling Dialect from Social Bias via Multitask Learning to Improve Fairness - Spliethöver, Maximilian; Menon, Sai Nikhil; Wachsmuth, Henning (Findings of the Association for Computational Linguistics: ACL 2024)
Dialects introduce syntactic and lexical variations in language that occur in regional or social groups. Most NLP methods are not sensitive to such variations. This may lead to unfair behavior of the methods, conveying negative bias towards dialect speakers. While previous work has studied dialect-related fairness for aspects like hate speech, other aspects of biased language, such as lewdness, remain fully unexplored. To fill this gap, we investigate performance disparities between dialects in the detection of five aspects of biased language and how to mitigate them. To alleviate bias, we present a multitask learning approach that models dialect language as an auxiliary task to incorporate syntactic and lexical variations. In our experiments with African-American English dialect, we provide empirical evidence that complementing common learning approaches with dialect modeling improves their fairness. Furthermore, the results suggest that multitask learning achieves state-of-the-art performance and helps to detect properties of biased language more reliably.

Time-bin entanglement in the deterministic generation of linear photonic cluster states - Bauch, David; Köcher, Nikolas; Heinisch, Nils; Schumacher, Stefan (APL Quantum)
We theoretically investigate strategies for the deterministic creation of trains of time-bin entangled photons using an individual quantum emitter described by a Λ-type electronic system. We explicitly demonstrate the theoretical generation of linear cluster states with substantial numbers of entangled photonic qubits in full microscopic numerical simulations. The underlying scheme is based on the manipulation of ground state coherences through precise optical driving. One important finding is that the most easily accessible quality metrics, the achievable rotation fidelities, fall short in assessing the actual quantum correlations of the emitted photons in the face of losses. To address this, we explicitly calculate stabilizer generator expectation values as a superior gauge for the quantum properties of the generated many-photon state. With widespread applicability in other emitter and excitation–emission schemes also, our work lays the conceptual foundations for an in-depth practical analysis of time-bin entanglement based on full numerical simulations with predictive capabilities for realistic systems and setups, including losses and imperfections. The specific results shown in the present work illustrate that with controlled minimization of losses and realistic system parameters for quantum-dot type systems, useful linear cluster states of significant lengths can be generated in the calculations, discussing the possibility of scalability for quantum information processing endeavors.

Organic Room-Temperature Polariton Condensate in a Higher-Order Topological Lattice - Bennenhei, Christoph; Shan, Hangyong; Struve, Marti; Kunte, Nils; Eilenberger, Falk; Ohmer, Jürgen; Fischer, Utz; Schumacher, Stefan; Ma, Xuekai; Schneider, Christian; Esmann, Martin (ACS Photonics)

Swing-up dynamics in quantum emitter cavity systems: Near ideal single photons and entangled photon pairs - Heinisch, Nils; Köcher, Nikolas; Bauch, David; Schumacher, Stefan (Physical Review Research)
In the SUPER scheme (Swing-UP of the quantum EmitteR population), excitation of a quantum emitter is achieved with two off-resonant, red-detuned laser pulses. This allows the generation of high-quality single photons without the need of complex laser stray light suppression or careful spectral filtering. In the present work, we extend this promising method to quantum emitters, specifically semiconductor quantum dots, inside a resonant optical cavity. A significant advantage of the SUPER scheme is identified in that it eliminates re-excitation of the quantum emitter by suppressing photon emission during the excitation cycle. This, in turn, leads to almost ideal single-photon purity, overcoming a major factor typically limiting the quality of photons generated with quantum emitters in high-quality cavities. We further find that for cavity-mediated biexciton emission of degenerate photon pairs, the SUPER scheme leads to near-perfect biexciton initialization with very high values of polarization entanglement of emitted photon pairs. Published by the American Physical Society 2024

Topological edge and corner states in coupled wave lattices in nonlinear polariton condensates - Schneider, Tobias; Gao, Wenlong; Zentgraf, Thomas; Schumacher, Stefan; Ma, Xuekai (Nanophotonics)
Abstract Topological states have been widely investigated in different types of systems and lattices. In the present work, we report on topological edge states in double-wave (DW) chains, which can be described by a generalized Aubry-André-Harper (AAH) model. For the specific system of a driven-dissipative exciton polariton system we show that in such potential chains, different types of edge states can form. For resonant optical excitation, we further find that the optical nonlinearity leads to a multistability of different edge states. This includes topologically protected edge states evolved directly from individual linear eigenstates as well as additional edge states that originate from nonlinearity-induced localization of bulk states. Extending the system into two dimensions (2D) by stacking horizontal DW chains in the vertical direction, we also create 2D multi-wave lattices. In such 2D lattices multiple Su–Schrieffer–Heeger (SSH) chains appear along the vertical direction. The combination of DW chains in the horizonal and SSH chains in the vertical direction then results in the formation of higher-order topological insulator corner states. Multistable corner states emerge in the nonlinear regime.

Manipulating spectral topology and exceptional points by nonlinearity in non-Hermitian polariton systems - Wingenbach, Jan; Schumacher, Stefan; Ma, Xuekai (Physical Review Research)
Exceptional points (EPs), with their intriguing spectral topology, have attracted considerable attention in a broad range of physical systems, with potential sensing applications driving much of the present research in this field. Here, we investigate spectral topology and EPs in systems with significant nonlinearity, exemplified by a nonequilibrium exciton-polariton condensate. With the possibility to control loss and gain and nonlinearity by optical means, this system allows for a comprehensive analysis of the interplay of nonlinearities (Kerr type and saturable gain) and non-Hermiticity. Not only do we find that EPs can be intentionally shifted in parameter space by the saturable gain, but we also observe intriguing rotations and intersections of Riemann surfaces and find nonlinearity-enhanced sensing capabilities. With this, our results illustrate the potential of tailoring spectral topology and related phenomena in non-Hermitian systems by nonlinearity. Published by the American Physical Society 2024

Novel Phosphazenium Tetrafluoroborate Dopant Enables Efficient and Thermally Stable n‐Doped Organic Semiconductors - Wei, Huan; Guo, Jing; Liu, Heng; Wu, Tong; Chen, Ping‐An; Dong, Chuanding; Wang, Shu‐Jen; Schumacher, Stefan; Bai, Yugang; Lei, Ting; Wang, Suhao; Hu, Yuanyuan (Advanced Electronic Materials)
Abstract Thermal stability is crucial for doped organic semiconductors (OSCs) and their applications in organic thermoelectric (OTE) devices. However, the capacity of n‐dopants to produce thermally stable n‐doped OSC films has not been thoroughly explored, with few reports of high thermal stability. Here, a novel n‐dopant, phosphazenium tetrafluoroborate (P 2 BF 4 ) is introduced, which effectively induces n‐doping in N2200, P(PzDPP‐CT2) and several other commonly used OSCs. Remarkably, the electrical conductivity of P 2 BF 4 ‐doped OSC films remains almost unchanged even after heating at temperatures > 150 °C for 24 h, far superior to the films doped with benchmark N‐DMBI. The exceptional thermal stability observed in P 2 BF 4 ‐doped P(PzDPP‐CT2) films allows for stable operation of the corresponding organic thermoelectric devices at 150 °C for 16 h, a milestone not previously achieved. This study offers valuable insights into the development of n‐dopants capable of producing OSCs with outstanding thermal stability, paving the way for the practical realization of OTE devices with enhanced operation stability.

Dynamics of Electron–Hole Coulomb Attractive Energy and Dipole Moment of Hot Excitons in Donor–Acceptor Polymers - Bauch, Fabian; Dong, Chuan-Ding; Schumacher, Stefan (The Journal of Physical Chemistry C)

Charge transfer in superbase n-type doping of PCBM induced by deprotonation - Dong, Chuan-Ding; Bauch, Fabian; Hu, Yuanyuan; Schumacher, Stefan (Physical Chemistry Chemical Physics)
Charge transfer mechanism in the deprotonation-induced n-type doping of PCBM.

Photochemical Reaction Enabling the Engineering of Photonic Spin–Orbit Coupling in Organic-Crystal Optical Microcavities - Liang, Qian; Ma, Xuekai; Gu, Chunling; Ren, Jiahuan; An, Cunbin; Fu, Hongbing; Schumacher, Stefan; Liao, Qing (Journal of the American Chemical Society)

An Empirical Examination of the Evaluative AI Framework - Kornowicz, Jaroslaw (arXiv)
This study empirically examines the "Evaluative AI" framework, which aims to enhance the decision-making process for AI users by transitioning from a recommendation-based approach to a hypothesis-driven one. Rather than offering direct recommendations, this framework presents users pro and con evidence for hypotheses to support more informed decisions. However, findings from the current behavioral experiment reveal no significant improvement in decision-making performance and limited user engagement with the evidence provided, resulting in cognitive processes similar to those observed in traditional AI systems. Despite these results, the framework still holds promise for further exploration in future research.

A Paradigm to Investigate Social Signals of Understanding and Their Susceptibility to Stress - Paletschek, Jonas (12th International Conference on Affective Computing & Intelligent Interaction)
In human-machine explanation interactions, such as tutoring systems or customer support chatbots, it is important for the machine explainer to infer the human user's understanding. Nonverbal signals play an important role for expressing mental states like understanding and confusion in these interactions. However, an individual's expressions may vary depending on other factors. In cases where these factors are unknown, machine learning methods that infer understanding from nonverbal cues become unreliable. Stress for example has been shown to affect human expression, but it is not clear from the current research how stress affects the expression of understanding. To address this gap, we design a paradigm that induces understanding and confusion through game rule explanations. During the explanations, self-perceived understanding and confusion are annotated by the participants. A stress condition is also introduced to enable the investigation of changes in the expression of social signals under stress. We conducted a study to validate the stress induction and participants reported a statistically significant increase in stress during the stress condition compared to the neutral control condition. Additionally, feedback from participants shows that the paradigm is effective in inducing understanding and confusion. This paradigm paves the way for further studies investigating social signals of understanding to improve human-machine explanation interactions for varying contexts.
Keywords: Understanding; Nonverbal Social Signals; Stress Induction; Explanation; Machine Learning Bias

Explainable AI for Audio and Visual Affective Computing: A Scoping Review - Johnson, David; Hakobyan, Olya; Paletschek, Jonas; Drimalla, Hanna (IEEE Transactions on Affective Computing)
ffective computing often relies on audiovisual data to identify affective states from non-verbal signals, such as facial expressions and vocal cues. Since automatic affect recognition can be used in sensitive applications, such as healthcare and education, it is crucial to understand how models arrive at their decisions. Interpretability of machine learning models is the goal of the emerging research area of Explainable AI (explainable AI (XAI)). This scoping review aims to survey the field of audiovisual affective machine learning to identify how XAI is applied in this domain. We first provide an overview of XAI concepts relevant to affective computing. Next, following the recommended PRISMA guidelines, we perform a literature search in the ACM, IEEE, Web of Science and PubMed databases. After systematically reviewing 1190 articles, a final set of 65 papers is included in our analysis. We quantitatively summarize the scope, methods and evaluation of the XAI techniques used in the identified papers. Our findings show encouraging developments for using XAI to explain models in audiovisual affective computing, yet only a limited set of methods are used in the reviewed works. Following a critical discussion, we provide recommendations for incorporating interpretability in future work for affective machine learnin

What you need to know about a learning robot: Identifying the enabling architecture of complex systems - Beierling, Helen; Richter, Phillip; Brandt, Mara; Terfloth, Lutz; Schulte, Carsten; Wersing, Heiko; Vollmer, Anna-Lisa (Cognitive Systems Research)
Nowadays we deal with robots and AI more and more in our everyday life. However, their behavior is not always apparent to most lay users, especially in error situations. This can lead to misconceptions about the behavior of the technologies being used. This in turn can lead to misuse and rejection by users. Explanation, for example through transparency, can address these misconceptions. However, explaining the entire software or hardware would be confusing and overwhelming for users. Therefore, this paper focuses on the ‘enabling’ architecture. It describes those aspects of a robotic system that may need to be explained to enable someone to use the technology effectively. Furthermore, this paper deals with the ‘explanandum’, i.e. the corresponding misunderstandings or missing concepts of the enabling architecture that need to be clarified. Thus, we have developed and are presenting an approach to determine the ‘enabling’ architecture and the resulting ‘explanandum’ of complex technologies.
Keywords: Robotics HRI Explainability Didactics Didactic reconstruction

Advancing Human-Robot Collaboration: The Impact of Flexible Input Mechanisms - Beierling, Helen; Loos, Kira; Helmert, Robin; Vollmer, Anna-Lisa
This position paper calls for an increase in the number and flexibility of input mechanisms in user-robot in- teractions, highlighting their potential to enhance learning algo- rithms through user feedback. Moreover, we argue that refining interfaces, interactions, and systems is crucial for the optimal integration of mechanisms into learning processes. Our call to research involves the development of interfaces that enable flexible mechanisms, and the mechanisms interactions can benefit most from, and the algorithmic incorporation of user input. This aims to advance the adaptability and responsiveness of robotic systems in human-centric environments

Influence of Dispersion Gas and Resulting Reaction Zone on the Particle Formation in Spray Flame Synthesis (Presentation) - Massopo, Orlando; Schmid, Hans-Joachim; Reddemann, Manuel; Kneer, Reinhold; Bieber, Malte

Untersuchung des Lösungsmitteleinflusses auf die Synthese von Manganoxid-Nanopartikeln in der Flammenspraypyrolyse - Zink, Timm Florian; Massopo, Orlando; Jesinghausen, Steffen; Schmid, Hans-Joachim

Einfluss der Zerstäubungsparameter auf die Partikelbildung und die Eigenschaften der Endproduktpulver (Studienarbeit) - El Gabbouhi, Abderazzak; Massopo, Orlando; Jesinghausen, Steffen; Schmid, Hans-Joachim

Understanding and Improving Triplet Exciton Transfer in Sensitized Silicon Solar Cells - Krenz, Marvin; Sanna, Simone; Gerstmann, Uwe; Schmidt, Wolf Gero (The Journal of Physical Chemistry C)

"Was heißt das, Mama?" Die Familie als Ort von Sprachaneignung und mehrsprachigen Praktiken am Beispiel einer türkisch-deutsch-sprachigen Familie - Ballweg, Sandra (Zeitschrift für Interaktionsforschung in DaFZ)